Insight and responsibility: ethics in pain medicine and palliative care - Gallagher, Rollin (Henry Stewart Talks, 2009)
The nature of chronic pain, pain patients, and the system we practice in creates ethical issues for us all, Diagnosis: there are many painful diseases and pain diseases, What is pain?, Beginning to end: the chronic pain cycle, The challenge: social, conscious and provider factors, Clinical reasoning, ethics and clinical practice management, Clinical metrics: efficacy and effectiveness, Effects of chronic pain on individual patients that might influence treatment outcomes, Insight and responsibility, Scope of ethics, Pain management, Managing levels of complexity to provide ethical community practice, Pain treatment continuum, Pain medicine and primary care community rehabilitation model, Pain care, 2020?, Integrating ethics into clinical decision-making in pain medicine and palliative care medicine in the 21st century, Beneficence, Nonmaleficence, Autonomy, Justice, Double effect